2013
DOI: 10.1177/0268355513496991
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous radiofrequency ablation and combined foam sclerotherapy treatment of multiple refluxing perforator veins in a Klippel-Trenaunay syndrome patient

Abstract: We describe an unusual pattern of venous abnormality and the use of endovenous radiofrequency ablation, using the TRans-Luminal Occlusion of Perforator technique to treat multiple refluxing perforators in a 29-year-old patient with Klippel-Trenaunay syndrome. Klippel-Trenaunay syndrome is a rare congenital anomaly characterised by a triad of features including unilateral limb overgrowth, venous varicosities and capillary malformations of the affected limb. Ultrasound findings demonstrated 22 incompetent perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…In 2014, Harris et al showed that RFA can be safely and effectively used for obliteration of perforating veins in KTS patients. Data from this study showed a significant symptomatic improvement following staged and multimodal treatment of perforating veins that included RFA combined with sclerotherapy 84 .…”
Section: Treatmentmentioning
confidence: 67%
“…In 2014, Harris et al showed that RFA can be safely and effectively used for obliteration of perforating veins in KTS patients. Data from this study showed a significant symptomatic improvement following staged and multimodal treatment of perforating veins that included RFA combined with sclerotherapy 84 .…”
Section: Treatmentmentioning
confidence: 67%
“…Nevertheless, venous duplex ultrasonography helps to differentiate the involvement of venous or arterial component. The identification also helps to address the problem by various modes like radiofrequency ablation before the surgery to avoid intraoperative catastrophic complication [12]. If intramedullary involvement is noted, then it is wiser to have total knee replacement under navigation which precludes the use of an intramedullary femoral guide [3].…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-directed embolization using coils, particulates, or sclerotherapy may be performed in small arteriovenous fistulas [3]. Foam sclerotherapy and endovenous radiofrequency ablation may be performed for perforating venous insufficiency [22].…”
Section: Discussionmentioning
confidence: 99%